Mycobacterium tuberculosis multi-drug-resistant strain M induces IL-17+ IFNγ- CD4+ T cell expansion through an IL-23 and TGF-β-dependent mechanism in patients with MDR-TB tuberculosis - Basile, Juan Ignacio (2016)
We have previously reported that T cells from patients with multidrug-resistant tuberculosis (MDR-TB) express high levels of IL-17 in response to the MDR strain M(Haarlem family) of Mycobacterium tuberculosis (M.tuberculosis). Herein, we explore the pathways involved in the induction of h17 cells in MDR-TB patients and healthy tuberculin reactors (PPD+HD) by the M strain and the laboratory strain H37Rv. Our results show that IL-1β and IL-6 are crucial for the H37Rv and M-induced expansion of IL-17+IFNγ¯ and IL-17+IFNγ+ in CD4+ T cells from MDR-TB and PPD+HD. IL-23 plays an ambiguous role in Th1 and Th17 profiles: alone, IL-23 is responsible for M.tuberculosis induced IL-17 and IFNγ expression in CD4+ T cells from PPD+HD whereas, together with TGF-β, it promotes IL-17+IFNγ¯ expansion in MDR-TB. In fact, spontaneous and M.tuberculosis-induced TGF-β secretion is increased in cells from MDR-TB being theM strain the highest inducer. Interestingly, TLR-2 signaling mediates the expansion of IL-17+IFNγ¯ cells and the enhancement of latency-associated protein (LAP) expression in CD14+ and CD4+ T cells from MDR-TB, which suggests that M strain promotes IL-17+IFNγ¯ T cells through a strong TLR-2-dependent TGF-β production by antigenpresenting cells and CD4+ T cells. Finally, CD4+ T cells from MDR-TB patients infected with MDR Haarlem strains show higher IL-17+IFNγ¯ and lower IL-17+IFNγ+ levels than LAM-infected patients. The present findings deepen our understanding on the role of IL-17 in MDR-TB and highlight the influence of the genetic background of the infecting M.tuberculosis strain on the ex vivo Th17 response.